Analisis Pelaksanaan E-office dalam Pengelolaan Surat di Kantor Suku Dinas Lingkungan Hidup Kota Administrasi Jakarta Pusat - Maya Agriyani Putri; Sri Kartikowati; Ria Rahma Nida (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study aims to analyze the implementation of the electronic office (e-office) system in correspondence management and to identify the challenges and efforts undertaken in its application at the Environmental Agency of Central Jakarta Administrative City. The background of this research is the increasing demand for digital transformation in public administration, which requires government institutions to adopt electronic systems to improve efficiency and administrative order. This study employs a descriptive qualitative method with a case study approach. Data were collected through interviews with four participants, direct observation, literature review, and documentation. The findings indicate that the e-office system has been utilized in the registration, recording, and distribution of incoming and outgoing letters. In the management of incoming mail, documents are first entered into the system, then printed for manual disposition by the head of the office, and subsequently re-entered into the system based on the disposition results. For outgoing mail, the drafting and submission process is conducted through the system, while the signing process is still performed manually. The challenges encountered include network disruptions, limited employee understanding of the system, and inadequate supporting facilities. Efforts to address these issues include regular system maintenance, improvement of supporting infrastructure, and training programs for employees. This study provides an overview of the implementation of e-office in supporting correspondence management and strengthening administrative order within government institutions, and highlights the importance of technological readiness and human resource competence in optimizing digital-based administrative systems.